Tingkat Kenyamanan Pejalan Kaki Berdasarkan Global Walkability Index Terhadap Pemanfaatan dan Desain Trotoar Jalan - Siti Rahmah Nurbayinah; Ida Farida (Institut Teknologi Garut, 2026)
Pedestrian facilities along Ahmad Yani Street in Garut Regency have undergone a change in function due to the increasing activities of street vendors (PKL). In addition to being occupied by street vendors, sidewalks are also used as parking spaces. This study aims to identify the physical condition of pedestrian facilities, compare the existing conditions with the standards set forth in the Circular Letter of the Minister of Public Works and Housing (PUPR) No. 02/SE/M/2018 Pd 03-2017-B on Technical Planning of Pedestrian Facilities, assess the comfort level of pedestrians based on user perception, and determine the walkability score evaluated by users using nine parameters of the Global Walkability Index (GWI). The research employs a qualitative method, as the nature of the Global Walkability Index (GWI) is perceptual—meaning the assessment is based on users’ perceptions to understand the condition of pedestrian facilities in the study area. The results show that the existing pedestrian facilities along Ahmad Yani Street are largely unavailable, and some that exist do not meet the required standards. User perception results indicate that the pedestrian paths are fairly comfortable to use. However, field observations reveal several obstacles that disrupt pedestrian comfort, such as the presence of street vendors and illegal parking. Furthermore, the walkability scores based on user assessments are as follows: Segment 1 – 42.25; Segment 2 – 43.2; Segment 3 – 43.1; and Segment 4 – 42.2. These values fall into the red category, indicating that the area is unsuitable for walking. This study proposes a pedestrian facility design that complies with applicable standards, as well as recommendations for the provision and improvement of pedestrian paths, including main and supporting facilities along Ahmad Yani Street. The suggested improvements are expected to serve as considerations for the Garut Regency Government in enhancing pedestrian infrastructure.